Case Report: Contrasting outcomes and use of desmosine to monitor two patients treated with plasma cell-directed chemotherapy for gammopathy-driven pulmonary elastolysis in acquired cutis laxa - Lee, Lydia; Fosbury, Emma; Popat, Rakesh; Yong, Kwee; Wechalekar, Ashutosh; Brown, Jeremy S.; Huang, Jeffrey; Mcbride, Sandy; Hurst, John R. (Frontiers in Hematology, 2025)
Acquired cutis laxa (ACL) is a rare connective tissue disorder that is characterised by loose, pendulous skin and can be associated with systemic elastolysis and plasma cell dyscrasias (PCD). While myeloma therapy has been used for these patients, experience is limited, particularly when organ dysfunction limits a patient’s tolerance of chemotherapy. We present two cases of ACL with progressive pulmonary emphysema that received treatment for coexisting PCD, resulting in differing outcomes. For the first time, we also monitored desmosine as a direct measurement of elastolysis throughout treatment and suggest that this may be useful for guiding therapy in these rare and complex patients.